The Impact of the Chinese Political System on Shaping Foreign Policy towards the Maghreb (Al-Farooq Journal of Sciences, 2026)
This study examines how China’s political system shapes its foreign behavior, focusing on its policy toward the Maghreb countries. It argues that China’s foreign policy cannot be understood without considering its internal political structure—dominated by the Communist Party, socialist principles with Chinese characteristics, and centralized yet pragmatic decision-making. The study highlights that China’s external conduct is driven by both domestic factors, such as institutional structure and regime stability, and external ones, including global and regional dynamics. In dealing with the Maghreb, China pursues a pragmatic, economically open, and non-ideological approach aligned with its political philosophy. The research concludes that the Chinese political system plays a decisive role in defining the country’s diplomatic strategies, particularly in regions of strategic importance like the Maghreb, which serves as a key link in the Belt and Road Initiative and a gateway to Africa and Europe.